THE EFFECTS OF CRUDE RECOMBINANT VIRAL PROTEIN VACCINES AGAINST GROUPER SLEEPY DISEASE IRIDOVIRUS (GSDIV) ON HUMPBACK GROUPER (Cromileptes altivelis) - Ketut Mahardika; Indah Mastuti (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2015)
Infection of Megalocytivirus cause serious mass mortality in marine fish in South East Asian countries. The aim of this study was to produce recombinant of GSDIV capsid protein and its protection to humpback grouper Cromileptes altivelis against grouper sleepy disease iridovirus (GSDIV). A major capsid protein (MCP) was selected for use as a crude subunit vaccines. This gene target (MCP) was inserted to the protein expression system vector of pET SUMO and cloned in cells bacteria Escherichia coli strain BL-21. The MCP was succeded to be induced using 1 mM of IPTG. Results of protein analysis using MALDI TOF-TOF indicated that the MCP has measurement of 49.566 kDa with PI index of 6.00, and contained 453 amino acids. BLAST homology analysis exhibited that the amino acid sequence of the MCP showed high similarity with MCP of Red Sea Bream Iridovirus (RSIV). E. coli expressing MCP protein was inactivated using 0.03% formalin overnight and washed using PBS. The inactivated E. coli as a crude subunit vaccine was then injected intramuscularly to humpback grouper juveniles. Subsequently, the juveniles were challenged tested with GSDIV. The juveniles vaccinated with the MCP recombinant bacteria showed significantly higher survival rates than control those vaccinated with PBS. Thus, the MCP fusion protein is considered as a potential vaccine against GSDIV infections in grouper.